2010
DOI: 10.1016/j.bbi.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory role of dopamine: An update

Abstract: The neurotransmitter dopamine (DA) is an important molecule bridging the nervous and immune systems. DA through autocrine/paracrine manner modulates the functions of immune effector cells by acting through its receptors present in these cells. DA also has unique and opposite effects on T cell functions. Although DA activates naïve or resting T cells, but it inhibits activated T cells. In addition, changes in the expression of DA receptors and their signaling pathways especially in T cells are associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
213
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(224 citation statements)
references
References 43 publications
(97 reference statements)
4
213
0
7
Order By: Relevance
“…During the past two decades, several studies have shown the capability of several neurotransmitters to regulate the function and differentiation of immune cells, including acetyl-choline, serotonin, glutamate, and dopamine (DA) among others (11)(12)(13)(14)(15)(16)(17)(18). Regarding expression of DA receptors (DARs) in immune cells, these receptors have been found not only in cells of the innate immune response such as dendritic cells (DCs), NK cells, macrophages/monocytes and granulocytes (19)(20)(21) but also in cells of the adaptive immune response such as B cells, CD8 + T cells, and CD4 + T cells (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
“…During the past two decades, several studies have shown the capability of several neurotransmitters to regulate the function and differentiation of immune cells, including acetyl-choline, serotonin, glutamate, and dopamine (DA) among others (11)(12)(13)(14)(15)(16)(17)(18). Regarding expression of DA receptors (DARs) in immune cells, these receptors have been found not only in cells of the innate immune response such as dendritic cells (DCs), NK cells, macrophages/monocytes and granulocytes (19)(20)(21) but also in cells of the adaptive immune response such as B cells, CD8 + T cells, and CD4 + T cells (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
“…In addition to its conventional role in the brain, recent reports indicate that DA also controls several functions in the periphery (8,9). DA has been shown to regulate behavior, movement, and cardiovascular, renal, endocrine, gastrointestinal, and immune functions (8)(9)(10). Normal blood vessels are supplied by sympathetic nerves, and neurotransmitters released from these nerve endings regulate many critical vascular functions (8,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…mune system as well as a mediator produced and released by immune cells themselves [31]. Several studies now indicate the presence of DA D1, D2, D3, D4 and D5 receptors in normal human leukocytes.…”
Section: Fig 2 Clinical and Macroscopic Features Of Iodoacetamide-imentioning
confidence: 99%